Deportacja ludności polskiej w kwietniu 1940 r. w świetle dyrektyw NKWD i relacji wysiedlonych rodzin. Próba analizy porównawczej. - Łagojda, Krzysztof (Pamięć i Sprawiedliwość, 2015)
The Deportation of the Polish Population in the Light of the NKVD Directives and Testimonies of the Displaced Families. The Attempt at Comparative Analysis.The article was a result of belief in the need of detailed description of the deportation of the families whose relatives had been murdered by the troops of the Soviet security apparatus in Katyn and other places of the former USSR. The article is an attempt at the comparative analysis of the NKVD directives with the reports of the exiled. The author carried out multiple-hour interviews with the Katyn families and Siberian exiles who were deported to Kazakhstan in April 1940. Moreover, the author used the expansive literature of memoirs and diaries of those times. The text includes the aspect of displacement and journey of the families to the remote steppes of Kazakhstan. The author aimed at confronting official directives for the operational units of the NKVD carrying out displacements with the reality maintained in the memories of the exiled, and pointing to similarities and differences between the first and the second deportations. The author described in detail the act of the NKVD barging into the houses of the families subject to deportation, indicated the directives concerning the deportation which were frequently ignored by the functionaries of the Soviet security apparatus, presented the house searches and pointed to these NKVD behaviours which were unusual and beyond the routine procedures. The article also describes the transportation to railway stations and the detailed journey in freight cars. It also includes the aspects of meals, executing physiological needs, intimate hygiene and death during the long journey. In the closing part of the text, the author referred to the ongoing disputebetween historians and the Siberian exiles concerning the numbers of people deported in 1940-1941. He shortly characterised the major publications on that topic and referred tothe important studies of the ‘Karta’ Centre and the Institute of National Remembrance in the series of ‘The Index of the Repressed’ which aim, among others, at specifying the list ofnames of all Poles deported during the four great Soviet displacement actions.